2003
DOI: 10.1097/00005537-200301000-00017
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Tissue Engineering to Generate a Human‐Sized Auricle and Nasal Tip

Abstract: An adult human-sized auricle and nasal tip cartilaginous structure can be grown entirely in vitro using principles of tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…These methods have been used for engineering of elastic and nonarticular cartilage such as auricle [7,21,41], nose [8,21], and tympanic membrane [17]. Several shaped osteochondral constructs containing articular cartilaginous sections, for phalanx [20,35] and mandibular condyle [1], for example, have been fabricated.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been used for engineering of elastic and nonarticular cartilage such as auricle [7,21,41], nose [8,21], and tympanic membrane [17]. Several shaped osteochondral constructs containing articular cartilaginous sections, for phalanx [20,35] and mandibular condyle [1], for example, have been fabricated.…”
Section: Discussionmentioning
confidence: 99%
“…In other tissue engineering applications (Kamil et al, 2003;Kojima et al, 2003), polymers that gel at body temperatures successfully immobilized cells in vivo. In those examples, 30wt% solutions of Pluronic F127 were used.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue engineering is a promising strategy for treating cartilage defects, especially those with specific shapes [Langer and Vacanti, 1993]. Since Cao et al [1997] reported having generated cartilage in the shape of a human ear in a nude mice model, construction of an earshaped cartilage using chondrocytes has been further developed [Hardin, 1998;Haisch et al, 2002;Kamil et al, 2003;Shieh et al, 2004;Kusuhara et al, 2009;Zhou et al, 2011]. However, chondrocytebased cartilage tissue engineering presents inevitable problems of low cell yield from limited cartilage sources [Brittberg et al, 2003] and fast dedifferentiation of chondrocytes after being expanded in a monolayer [von der Mark et al, 1977;Benya and Shaffer, 1982;Elima and Vuorio, 1989].…”
Section: Introductionmentioning
confidence: 99%